Study of immobilization of bolaform ions on polymethacrylic acid - Urinova Zebo; Karimov Makhmud; Babaev Tuygun; Kambarov Asadjon; Rifky Mohamed; Abrolov Anvarjon (BIO Web of Conferences)
The study of the interactions of polyelectrolytes with organic ions, in particular bolaform ions, that is, having a mirror conformational chemical structural symmetry with respect to the centre of the molecule and exhibiting physiological activity, is particularly intriguing due to its potential for simulating biological processes and its implications for the development of novel polymer therapeutic systems. These systems possess unique features that distinguish them from low-molecular-weight medicines. Of the large assortment of polymers used for these purposes, the most convenient “substrate” is considered to be synthetic polyelectrolytes that are easily adjustable during production, possessing active functional groups for binding organic ions and the property of good solubility in water. The objects of research were an antibacterial agent, aethonium, and a drug, imidocarb, widely used in veterinary practice, which, when dissolved in water, forms complex bolaform cations and an industrially developed polymer, polymethacrylic acid. In order to develop a prolonged dosage form for veterinary medicine, the binding of these substances to a selected synthetic polymer was studied using physical and chemical methods. IR spectroscopy has proven the “soft” immobilization of the studied organic ions on polymethacrylic acid. Factors influencing the immobilization process have been established: the ratio of reagents, the nature of the solvent and temperature, and the thermodynamic parameters of the studied process.